Localization of Mycobacterium tuberculosis topoisomerase I C-terminal sequence motif required for inhibition by endogenous toxin MazF4 - Garcia, Pamela K.; Martinez Borrero, Rosemarie; Annamalai, Thirunavukkarasu; Diaz, Esnel; Balarezo, Steve; Tiwari, Purushottam B.; Tse-Dinh, Yuk-Ching (Frontiers in Microbiology, 2022)
Only about half the multi-drug resistant tuberculosis (MDR-TB) cases are successfully cured. Thus, there is an urgent need of new TB treatment against a novel target. Mycobacterium tuberculosis (Mtb) topoisomerase I (TopA) is the only type IA topoisomerase in this organism and has been validated as an essential target for TB drug discovery. Toxin-antitoxin (TA) systems participate as gene regulators within bacteria. The TA systems contribute to the long-term dormancy of Mtb within the host-cell environment. Mtb’s toxin MazF4 (Rv1495) that is part of the MazEF4 TA system has been shown to have dual activities as endoribonuclease and topoisomerase I inhibitor. We have developed a complementary assay using an Escherichia coli strain with temperature-sensitive topA mutation to provide new insights into the MazF4 action. The assay showed that E. coli is not sensitive to the endoribonuclease activity of Mtb MazF4 but became vulnerable to MazF4 growth inhibition when recombinant Mtb TopA relaxation activity is required for growth. Results from the complementation by Mtb TopA mutants with C-terminal deletions showed that the lysine-rich C-terminal tail is required for interaction with MazF4. Site-directed mutagenesis is utilized to identify two lysine residues within a conserved motif in this C-terminal tail that are critical for MazF4 inhibition. We performed molecular dynamics simulations to predict the Mtb TopA-MazF4 complex. Our simulation results show that the complex is stabilized by hydrogen bonds and electrostatic interactions established by residues in the TopA C-terminal tail including the two conserved lysines. The mechanism of Mtb TopA inhibition by MazF4 could be useful for the discovery of novel inhibitors against a new antibacterial target in pathogenic mycobacteria for treatment of both TB and diseases caused by the non-tuberculosis mycobacteria (NTM).